Mutation breeding in chickpea : perspectives and prospects for food security - Kozgar, M. Imran (De Gruyter Open, 2014)
Research on induced mutagenesis of pulses including chickpea is less common compared to the one on cereals and henceforth the present work is pioneering in the field. The chickpea is one of the largest grown pulse crops in India. The author hopes that his book will help to advance studies on pulses, and in the long-term, to reduce food insecurity and malnutrition persisting in various developing countries.